Study on the oiling-out and crystallization for the purification of idebenone - Lu, Jie (2013)
Oiling-out, also termed as demixing or liquid–liquid phase separation (LLPS), frequently occurs in the crystallization process of pharmaceuticals and normally results in slow crystal growth, uncontrollable crystal morphology, and low purity of products. In this work, the oiling-out and cooling crystallization of idebenone were investigated. The cooling crystallization and the purity of its products were found to depend upon whether an oiling-out occurred in the course of cooling. At low initial concentrations (e.g., 12 mg/mL), oiling-out did not take place, and the crystallization products possessed higher purity. At moderate initial concentrations (e.g., 25 mg/mL) small quantities of oil droplets formed and then coalesced into larger droplets, which subsequently crystallized into products with lower purity. When high initial concentrations (e.g., 31 mg/mL) were employed, large quantities of oil droplets formed a stable oil phase, and thus no products could be harvested. In addition to initial concentration, other parameters such as solvent, cooling rate, and seeding also affected the occurrence of oiling-out. On the basis of the above results, the approach to purifying idebenone through cooling crystallization will be found.